Gravimetric phenotyping of whole plant transpiration responses to atmospheric vapour pressure deficit identifies genotypic variation in water use efficiency. (October 2016) - Ryan, Annette C.; Dodd, Ian C.; Rothwell, Shane A.; Jones, Ros; Tardieu, Francois; Draye, Xavier; Davies, William J.
Highlights: 100 well-watered maize genotypes demonstrated a 2-fold variation in whole plant water use efficiency (WUE). Two categories of transpiration response to varying VPD were identified. Genotypes showed either a linear increase in transpiration at all VPDs, or a non-linear response with a clear change point. The transpiration responses of plants on phenotyping platforms can be used to acceleratethe identification of high WUE plants. Abstract: There is increasing interest in rapidly identifying genotypes with improved water use efficiency, exemplified by the development of whole plant phenotyping platforms that automatically measure plant growth and water use. Transpirational responses to atmospheric vapour pressure deficit (VPD) and whole plant water use efficiency (WUE, defined as the accumulation of above ground biomass per unit of water used) were measured in 100 maize ( Zea mays L.) genotypes. Using a glasshouse based phenotyping platform with naturally varying VPD (1.5–3.8 kPa), a 2-fold variation in WUE was identified in well-watered plants. Regression analysis of transpiration versus VPD under these conditions, and subsequent whole plant gas exchange at imposed VPDs (0.8–3.4 kPa) showed identical responses in specific genotypes. Genotype response of transpiration versus VPD fell into two categories: 1) a linear increase in transpiration rate with VPD with low (high WUE) or high (low WUE) transpiration rate at all VPDs, 2) a non-linear response with a pronounced change point at low VPD (high WUE) or high VPD (low WUE). In the latter group, high WUE genotypes required a significantly lower VPD before transpiration was restricted, and had a significantly lower rate of transpiration in response to VPD after this point, when compared to low WUE genotypes. Change point values were significantly positively correlated with stomatal sensitivity to VPD. A change point in stomatal response to VPD may explain why some genotypes show contradictory WUE rankings according to whether they are measured under glasshouse or field conditions. Furthermore, this novel use of a high throughput phenotyping platform successfully reproduced the gas exchange responses of individuals measured in whole plant chambers, accelerating the identification of plants with high WUE.